Faktor Resiko Stunting Pada Anak Usia 0-5 Tahun di Indonesia: Scoping Review - Riansyah, Alvi; Ariestanti, Nurrachma; Rahmawati, Sri; Shabrina, R Maghfira Izzany; Gustiani, Ajeng; Kurnia, Mochamad Ilham; Maryati, Ida (Universitas Malahayati, 2026)
ABSTRACT Nutritional deficiencies in children will impact their growth and development. Currently, one of the global nutrition problems is stunting. To determine the risk factors for stunting in children aged 0-5 years in Indonesia. Scoping review by searching for articles in English published from 2015 to 2025 from four international databases. The main keywords used were “stunting”, “growth disorder”, “children”, “risk factors” and “Indonesia”. Based on 6 selected articles, twelve factors were found to influence the incidence of stunting. The factors are child, mother, home, inadequate complementary feeding, inadequate breastfeeding, poor quality food, food and water safety, infection, inadequate care, political economy, health and health care, and water, sanitation and environment. All of these factors may contribute to the incidence of stunting in Indonesia. It is necessary to improve health by providing health services and conducting health promotion as a prevention effort based on the factors found. Keywords: Children, Risk Factors, Indonesia, Stunting. ABSTRAK Kekurangan nutrisi pada anak akan berdampak pada pertumbuhan dan perkembangannya. Saat ini, salah satu masalah gizi yang sedang mendunia adalah stunting. Untuk mengetahui faktor resiko stunting pada anak usia 0-5 tahun di Indonesia. Untuk mengetahui faktor resiko stunting pada anak usia 0-5 tahun di Indonesia. Scoping review dengan mencari artikel dalam Bahasa Inggris yang diterbitkan tahun 2015 hingga 2025 dari empat database internasional. Kata kunci utama yang digunakan adalah “Stunting”, “Growth disorder”, “Children”, “Risk Factor” dan “Indonesia”.Berdasarkan 6 artikel terpilih didapatkan dua belas faktor yang dapat mempengaruhi kejadian stunting. Faktornya yakni faktor anak, ibu, rumah, pemberian makanan pendamping ASI yang tidak memadai, pemberian ASI yang tidak memadai, makanan berkualitas buruk, keamanan makanan dan air, infeksi, perawatan yang tidak memadai, ekonomi politik, Kesehatan dan perawatan kesehatan, dan air, sanitas dan lingkungan. Semua faktor tersebut dapat menyebabkan kejadian stunting di Indonesia. Perlu dilakukannya peningkatan kesehatan dengan menyediakan layanan kesehatan dan melakukan promosi kesehatan sebagai upaya pencegahan berdasarkan factor yang ditemukan. Kata Kunci: Anak, Faktor Risiko, Indonesia, Stunting.